Maternal Age and Infant Health - Cristina Borra; Libertad González; David Pati\~no (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2021)
We study the effects of maternal age on infant health. Age at birth has been increasing for the past several decades in many countries, and correlations show that health at birth is worse for children born to older mothers. In order to identify causal effects, we exploit school entry cutoffs and the empirical finding that women who are older for their cohort in school tend to give birth later. In Spain, children born in December start school a year earlier than those born the following January, despite being essentially the same age. We show that as a result, January-born women finish school later and are (several months) older when they marry and when they have their first child. We find no effect on educational attainment. We then compare the health at birth of the children of women born in January versus the previous December, using administrative, population-level data, and following a regression discontinuity design. We find small and insignificant effects on average weight at birth, but the children of January-born mothers are more likely to have very low birthweight. We interpret our results as suggestive of a causal effect of maternal age on infant health, concentrated in the left tail of the birthweight distribution, with older mothers more likely to give birth to (very) premature babies.
Keywords: 330; Maternal age; Infant health; School cohort